Ujednolicenie zasad odpowiedzialności karnej skarbowej za posługiwanie się fakturą fikcyjną i fakturą nierzetelną w celu wyłudzenia zwrotu podatku vat w aspekcie orzecznictwa sądowego - Rycielski, Radosław (Kwartalnik Prawa Podatkowego, 2016)
The article concerns the rules of fiscal penal responsibility for using unjust and fictional invoice with the purpose of wheedling tax return. There was taken into consideration most recent judicature referring to the issue of unifying of this responsibility. As results from it, the distinction between unjust and fictional invoice has no meaning in terms of dimunition of State Treasury income, because the intention of violator (as to issuing both ujnust and fictional invoice) leads in consequence to dimunition the public income and therefore there’s no practical meaning in this distinction, because these two types of invoice are the the documents against the actual state. The article concerns also the issues related to avoiding the fiscal penal responsibility for issuing of fictional invoice.